Proposal for design rules of axially loaded CFRP strengthened cold formed lipped channel steel sections - Kalavagunta S.; Naganathan S.; Bin Mustapha K.N. (2023)
Carbon fiber reinforced polymer (CFRP) composites are considered to have high performance and potential for use in strengthening, retrofitting and for the rehabilitation of structural sections. In this paper, design procedures are proposed for the axial load capacity of cold formed steel lipped channel columns strengthened with carbon fiber reinforced polymer (CFRP). For the purpose of validation, the results are based on the proposed design equation from the North American specification for the design of cold-formed steel structural members (AISI-2007) and Euro code for cold-formed members and sheeting (EC3-EN1993-1-3:2006) are compared against the experimental test data. The test results showed that the capacity of the columns are close to the theoretical values predicted by the AISI-2007 and EC 3 provisions. Some tested specimens showed reduced capacity and premature failure due to peeling and debonding of the CFRP from the steel. Various experimental investigations are suggested for future work to further validate and update the design equations. From the experimental studies, it has been observed that there is significant increase in strength due to CFRP strengthening. 2013 Elsevier Ltd.